156 Factors influencing recurrence in patients undergoing laparoscopic treatment for apparent early stage cervical cancer. (18th September 2019) - Artuso, V; Pinelli, C; Gisone, B; Borghi, C; Dri, M; Casarin, J; Ghezzi, F
Abstract : Objectives: To evaluate oncological outcomes and predictors of recurrence in patients undergoing laparoscopic treatment for apparent early stage cervical cancer (CC). Methods: A single-centre retrospective study was conducted among patients who had radical surgery for FIGO stage (2009) IA (positive LVSI) – IB1 at Women's and Children Hospital of Varese (Italy) between January 2006 and December 2018. Radical hysterectomy (Querleu and Morrow B-C1 Classification) with or without lymph node dissection according with tumour characteristics. Surgical and oncological outcomes were analysed. Results: Among 90 patients who met the inclusion criteria, 12 (13.3%) had recurrent disease (6 vault, 6 pelvis, 3 abdominal, 2 distant, 1 other), and 6 (6.7%) died of disease over the follow-up period (median follow-up 38.2 months). Surgical-related outcomes did not influence survival. Stage of disease has been found to be the main predictor of recurrence (p=0.03), while no association between positive lymph node and relapse was detected. Patients who had preoperative biopsy had a significant higher rate of recurrence in comparison to those undergoing conization (83.33% vs 16.67%, p=0.01). After stratification by tumour size, patients with stage IB1 CC undergoing preoperative conization had 0.37 relative risk of recurrence compared to those undergoing cervical biopsy (16.67% vs 38.89%, p=0.14). Conclusions: Preoperative conization might play a crucial role for patients undergoing laparoscopic treatment for early stage CC. Further studies are warranted to confirm our finding.